Pattern and Outcome of Preterm Newborns Admiited to NICU Bacha Khan Medical Complex /Gajju Khan Medical Complex Swabi - Muhammad Tariq; Ahmad, Waqar; Haji Gul; Inayat Ullah; Hussain, Saddam; Rasool, Muhammad Farhan (Indus Journal of Bioscience Research, 2025)
Prematurity remains a leading contributor to neonatal morbidity and mortality, particularly in low-resource countries such as Pakistan. Despite improvements in neonatal intensive care services, preterm infants continue to experience high rates of adverse outcomes. Identifying local determinants of neonatal morbidity and mortality is essential for targeted interventions. To determine the spectrum of morbidities and predictors of clinical outcomes among preterm neonates admitted to the Neonatal Intensive Care Unit (NICU) of Bacha Khan Medical Complex, Swabi.This prospective cohort study was conducted over 18 months (January 2024-June 2025) and included 221 preterm neonates (<37 weeks gestation). Data regarding gestational age, birth weight, gender, maternal and perinatal factors, major morbidities, oxygen requirement, duration of hospital stay, and outcomes were collected. Descriptive statistics and chi-square tests were applied using SPSS version 23, with p<0.05 considered significant. The mean gestational age was 31.6 ± 2.1 weeks and mean birth weight was 1558 ± 425 g. Most neonates were very preterm (34.4%) or moderate preterm (33%), and 58.8% were low birth weight. Sepsis (39.4%), jaundice (32.1%), congenital heart disease (8.6%), and oxygen requirement (59.2%) were the common morbidities. Overall, 62.9% of neonates improved while 37.1% expired. Mortality was significantly higher among extremely preterm and extremely low birth weight infants (p<0.001). Sepsis and congenital heart disease were also strongly associated with poor outcomes. Prematurity, low birth weight, sepsis, and congenital heart disease are major predictors of adverse outcomes among NICU-admitted neonates. Strengthening antenatal care, infection control practices, and NICU facilities is essential to further reduce neonatal mortality in this region.